PENGARUH KETEBALAN BATU KORAL PADA TANAH LEMPUNG DAN TANAH BERPASIR TERHADAP TEGANGAN LANGKAH DAN TEGANGAN SENTUH - Nova Suciawan, I Putu; Janardana, I Gusti Ngurah; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i01.p8, 2021)
Ground fault currents that flow in the disturbance area and in the switchyard area of the Substation create tension on the ground which can result in touch voltage and step voltage that exceed the allowable limits of human safety. The thickness of the coral rock affects the value of the touch voltage and step voltage. This research was conducted to determine the effect of the thickness of the coral rock on clay and sandy soil on stepvvoltage anddtouchvvoltage.The method used is by measuring coral, clay soils and sandy soils, then calculating thevvalue ofttouch voltageaand stepvvoltage based on the thickness of the coral used. The results of calculations and analysis of several thicknesses of coral stones used in clay soil, obtained the results of the touch voltage in the dry state of 153.5615 volts and in the wet state of 152.0702 volts, the results of the step voltage in the dry state 188.5057 volts and in the w et state 182 , 8265 volts. On sandy soil, the results of the touch voltage are 153.6893 volts in dry condition and 152.1981 volts in wet conditions, the results of the step voltage in dry conditions are 189.141 volts and in wet conditions 183.4349 volts.